PENGAWASAN INSPEKTORAT DAERAH DALAM MEWUJUDKAN AKUNTABILITAS PENGELOLAAN DANA DESA DI KABUPATEN MALAKA - Fetomalae, Michael Anjelo; Angi, Yohana Febiani; Oematan, Herly M. (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study aims to determine the supervisory function and constraints of the Inspectorate in realising the accountability of village fund management in Malaka Regency. The type of research used is descriptive qualitative with a case study approach with research informants inspectors, planning and finance sections and auditors of the inspectorate of Malaka Regency. This research focuses on the implementation of supervision by using data collection techniques in the form of in-depth interviews, observation, literature study and documentation. The data collected was analysed using Nvivo 12 software with the analysis method developed by Miles and Huberman. The results of this study indicate that the inspectorate has carried out supervision but not maximally due to the discovery of corruption cases that occur, one of the breakthroughs of the Inspectorate is a consultation clinic. There are three obstacles experienced by the Inspectorate, namely budget limitations, short audit time and inadequate infrastructure access.